Short-term low-protein diet during pregnancy alters islet area and protein content of phosphatidylinositol 3-kinase pathway in rats - SALVATIERRA,CRISTIANA S.B. (2015)
The phosphatidylinositol 3-kinase and mitogen-activated protein kinase pathways mediate β cell growth, proliferation, survival and death. We investigated whether protein restriction during pregnancy alters islet morphometry or the expression and phosphorylation of several proteins involved in the phosphatidylinositol 3-kinase and mitogen-activated protein kinase pathways. As controls, adult pregnant and non-pregnant rats were fed a normal-protein diet (17%). Pregnant and non-pregnant rats in the experimental groups were fed a low-protein diet (6%) for 15 days. Low protein diet during pregnancy increased serum prolactin level, reduced serum corticosterone concentration and the expression of both protein kinase B/AKT1 (AKT1) and p70 ribosomal protein S6 kinase (p70S6K), as well as the islets area, but did not alter the insulin content of pancreatic islets. Pregnancy increased the expression of the Src homology/collagen (SHC) protein and the extracellular signal-regulated kinases 1/2 (ERK1/2) independent of diet. ERK1/2 phosphorylation (pERK1/2) was similar in islets from pregnant and non-pregnant rats fed a low-protein diet, and was higher in islets from pregnant rats than in islets from non-pregnant rats fed a normal-protein diet. Thus, a short-term, low-protein diet during pregnancy was sufficient to reduce the levels of proteins in the phosphatidylinositol 3-kinase pathway and affect islet morphometry.